Mapping life Skills Development for the Language Classroom: Observations and Reflections - Sakib, Najmus (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The development of life skills is currently the primary goal of school education. Students‘ holistic development is facilitated by the development of life skills. Life skills are the mixture of thinking skills, emotional skills and social skills that helps the learners accomplish their daily requirements. The development of practical life skills is mostly overlooked at the school stage. The school places a high value on academic success. In order to prepare students to satisfy their own needs and deal with problems on their own, life skills development must be addressed at the school stage. The development of life skills is substandard at the school stage. Life skills development takes place as a separate course during the school years. However, the development of life skills should be interwoven with other educational subjects. Student life skills can be developed through the use of language. The classroom is the most easily accessible location for students, and it is where they spend the most of their time at school. Language classroom can be a most appropriate place for developing life skills among students. In view of the present context, this chapter is through light on concept of life skills including essential life skills for learners, need of developing life skills through language and exemplar life skills-based activities in language, transfer of life skills through language.